Effects of different cyclooxygenase inhibitors on prostaglandin E2 production, steroidogenesis and ovulation of bovine preovulatory follicles - Andreas VERNUNFT; Rebecca LAPP; Torsten VIERGUTZ; Joachim M. WEITZEL (The Society for Reproduction and Development, 2022)
Ovulation is an inflammation-like process, and cyclooxygenase-2 (COX-2)-dependent production of prostaglandin E2 (PGE2) is its key mediator. Balanced regulation of inflammatory processes in high-yielding dairy cows may be essential for physiological ovulation and fertility. This study aimed to elucidate the mechanisms underlying ovulation failure and cyst development after disturbing intrafollicular inflammatory cascades. Therefore, nonselective (indomethacin and flunixin-meglumine), COX-2 selective (meloxicam), and highly COX-2 selective (NS-398) inhibitors were injected into preovulatory follicles 16 h after administration of GnRH, and ovulation was monitored via ultrasound examination. Additionally, follicular fluid was collected after injection of indomethacin, meloxicam, and NS-398. Moreover, primary granulosa cell cultures from preovulatory follicles were prepared and treated with indomethacin, meloxicam, and NS-398. The concentrations of 17β-estradiol, progesterone, and prostaglandin E2 (PGE2) in the follicular fluid and cell supernatant were estimated. Indomethacin and flunixin-meglumine blocked ovulation, even at low doses, and led to ovarian cyst development. The selective and highly selective COX-2 inhibitors meloxicam and NS-398 were not effective in blocking ovulation. However, indomethacin, meloxicam, and NS-398 significantly and comparably reduced PGE2 concentration in vivo and in vitro (P < 0.05) but had no effect on estradiol or progesterone production. This may contradict the generally accepted hypothesis that PGE2 is a key mediator of ovulation and progesterone production. Our results suggest a connection between ovarian disorders and inflammatory actions in early postpartum cows.